Full STEAM ahead - Implications for Teacher Education in the Context of Curricular and Policy Reform in Ireland - Lovatt, James (Asia Research Network Journal of Education, 2021)
STEM and more recently STEAM have become core aspects of Government policy and educational reform throughout the world. There is a central focus on preparing citizens and graduates who have expertise in STEM disciplines to drive innovative societies and economic ambitions. In many cases these changing policies are in response to the opportunities and challenges of the fourth industrial revolution. In this paper, an overview of STEM policy and related curricular reform in Ireland is presented. Specific attention is paid to the importance of and implications of these policies for teacher education. It is argued that the role of the teacher, and by extension the role of teacher education, is now more complex. Challenges in preparing pre-service teachers (PSTs) to engage in pedagogical practices, including assessment, which they may not have experienced as learners are discussed. Additionally, it is proposed that there is a need to identify skills PSTs need to develop before they can effectively prepare their students for a changing society.